Quality of Available Mates, Education and Intra-Household Bargaining Power - Sonia Oreffice; Brighita Bercea (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper further explores the role of sex ratios on spouses bargaining power, by focusing on educational attainment in order to capture the qualitative aspect of mate availability. Using Census and Current Population Survey data for U.S. metropolitan areas in year 2000, a quality sex ratio is constructed by education brackets to test the effect on the intra-household bargaining power of couples in the corresponding education bracket. We argue that a relative shortage of suitably educated women in the spouses potential marriage market increases wives bargaining power in the household while it lowers their husbands. Additionally, we test the prediction that this bargaining power effect is greater as the assortative mating order by education increases. We consider a collective labor supply household model, in which each spouses labor supply is negatively related to their level of bargaining power. We find that higher relative shortage of comparably educated women in the couples metropolitan area reduces wives labor supply and increases their husbands. Also, the labor supply impact is stronger for couples in higher education groups. No such effects are found for unmarried individuals, which is consistent with bargaining theory.
Keywords: D12; J12; 330; Education; Intra-Household Bargaining Power; Labor Supply; Ehe; Verhandlungsmacht; Bildungsniveau; Arbeitsangebot; Matching; USA